2022
DOI: 10.1017/dmp.2022.153
|View full text |Cite
|
Sign up to set email alerts
|

Challenges Created by the COVID-19 Pandemic: Pediatric Emergency Medicine and Disaster Management Perspectives

Abstract: Objective: The COVID-19 pandemic has presented unique challenges to pediatric emergency medicine (PEM) departments. The purpose of this study was to identify these challenges and ascertain how centers overcame barriers in creating solutions to continue to provide high-quality care and keep their workforce safe during the early pandemic. Methods: This is a qualitative study based on semi-structured interviews with physicians in leadership positions who have disaster or emergency managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 35 publications
0
4
0
Order By: Relevance
“…The coronavirus disease 2019 (COVID-19) pandemic also introduced additional barriers to accessing healthcare services, particularly for non-critical or indirect clinical activities, such as preparatory activities. Furthermore, as process and practice standards evolved during the pandemic responses, the efficiency was reduced due to added infection control requirements and the additional accommodations put in place to ensure individual comfort levels of both staff and patients [10]. Virtual reality (VR) is one tool that can be used to help educate patients and their families about medical imaging and simulate the experience of being scanned without coming to the hospital for onsite preparation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…The coronavirus disease 2019 (COVID-19) pandemic also introduced additional barriers to accessing healthcare services, particularly for non-critical or indirect clinical activities, such as preparatory activities. Furthermore, as process and practice standards evolved during the pandemic responses, the efficiency was reduced due to added infection control requirements and the additional accommodations put in place to ensure individual comfort levels of both staff and patients [10]. Virtual reality (VR) is one tool that can be used to help educate patients and their families about medical imaging and simulate the experience of being scanned without coming to the hospital for onsite preparation [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Establishing recommendations at the national level might also ensure harmonization [ 29 ]: the pandemic has affected each country differently, with those nursing programs located in the most affected regions having been forced to revolutionize the curriculum, thus acquiring in-depth insights into the changes needed in the future, while to a different degree/extent there are those that have been required to enact fewer changes, thus preventing an understanding of how to design the nursing education in the post-pandemic era. Moreover, a part of embodying the lesson learned, redesigning nursing education based on agreed recommendations, may promote common standards of education, and create the basis on how to deal with future pandemic/catastrophic events by making the educational systems ready and prepared [ 30 , 31 ]. Therefore, the aim of this study was to identify a set of recommendations that can guide the Italian nursing education to move forward in the post-pandemic era.…”
Section: Introductionmentioning
confidence: 99%
“…11 More recent trends, including significantly increasing volumes of pediatric patients with behavioral health complaints, large fluctuations in patient volumes, the SARS-CoV-19 pandemic, and new transmission patterns of infectious diseases, have stressed pediatric EDs. [12][13][14][15][16][17] While patient volumes and mix do not change abruptly, they eventually reach a threshold that prompts pediatric EDs to innovate clinical operations models in response. These include increasing primary care utilization, transferring care for boarding patients to inpatient teams, increasing the care provided in triage, and creating alternative care sites for seeing patients.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have shown variability and gaps in exposure to core pediatric diagnoses during pediatric ED rotations 11 . More recent trends, including significantly increasing volumes of pediatric patients with behavioral health complaints, large fluctuations in patient volumes, the SARS‐CoV‐19 pandemic, and new transmission patterns of infectious diseases, have stressed pediatric EDs 12–17 . While patient volumes and mix do not change abruptly, they eventually reach a threshold that prompts pediatric EDs to innovate clinical operations models in response.…”
Section: Introductionmentioning
confidence: 99%